Enhance oil recovery by ultrasonic waves - Nur Syazwani binti Kenny Yusoff, Nur Syazwani (2009)
In oil reservoirs about 60% of the original oil in place remains as residual oil after primary and secondary oil recovery due to geological and physical factors. By means of improved oil recovery (lOR) methods, additional oil can be mobilized.